Unveiling the Modern Therapeutic Properties and Folk Medicinal Riches of Rubia cordifolia - Sharma, Diksha; Jain, Divya; Bhatia, Deepika (Recent Patents on Biotechnology, 2025)
<span class=
Keywords: Rubia cordifolia